Exploring the Impact of Planned Relocation on Agricultural Income Generation in Sri Lanka: A Case of Landslide Induced Resettlement in Y District - Naduni Jayasinghe; Nishara Fernando; Dilanthi Amaratunga; Richard Haigh; Kithugasmulle Lekamalage Wathsala Indeevarie Gunathilake (Journal of Regional and City Planning, 2022)
The recent global acknowledgement of the importance of disaster risk reduction (DRR) in steering the world towards sustainable development can be discerned in the Sendai Framework for DRR 2015-2030 and the 2030 Agenda for Sustainable Development. Ironically, certain DRR strategies like planned relocation have often undermined agricultural production, which is paramount for achieving certain Sustainable Development Goals (SDGs), such as ‘Zero Poverty’ and ‘Zero Hunger’. This paper explores the impact of planned relocation on the agricultural income generating activities of rural communities relocated under a landslide induced relocation program executed in the Y district of Sri Lanka. Further, it discusses the extent to which the outcomes of said relocation program comply with the Post-2015 Sustainable Development Agenda, thereby informing future policy directions towards planning, designing and executing DRR measures aimed at sustainable development. This study drew on a survey administered among 435 households who have been resettled under said project. The data was analyzed using the descriptive statistical method interactively with the Statistical Package for Social Sciences (SPSS) and the MS Excel software. The findings of this study show that relocation has generated unfavorable outcomes for relocatees who depended on agriculture as primary or subsidiary source of income. This group of relocatees was also characterized by pre-existing vulnerabilities, rendering it difficult for them to adapt to the risks and stresses caused by relocation. Agricultural income generating activities are particularly threatened by relocation initiatives, as such activities are reliant on immovable assets like land. Therefore, special attention should be paid to rebuilding livelihoods of agricultural communities in planning, designing and implementing relocation programs. Given the significance of agriculture in achieving certain SDGs, failure to do so will lend to dissonance between DRR measures and the 2030 Sustainable Development Agenda, subduing the efficacy of DRR in protecting development gains.